2024
DOI: 10.3389/fimmu.2024.1347259
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear cell composition and activation in blood and mucosal tissue of eosinophilic esophagitis

Eva Gruden,
Melanie Kienzl,
Dusica Ristic
et al.

Abstract: IntroductionEosinophilic esophagitis (EoE) is a chronic, inflammatory, antigen-driven disease of the esophagus. Tissue EoE pathology has previously been extensively characterized by novel transcriptomics and proteomic platforms, however the majority of surface marker determination and screening has been performed in blood due to mucosal tissue size limitations. While eosinophils, CD4+ T cells, mast cells and natural killer (NK) T cells were previously investigated in the context of EoE, an accurate picture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Also, single cell studies unraveled an enrichment in CD4 + T regulatory and Th 2 effector cells in the inflamed esophageal tissue (25). With the aim of exploring non-invasive biomarkers, the studies done in peripheral blood mononuclear cells (PBMCs) in active EoE patients demonstrated an increase in circulating CD4 + /CD8 + Tcell ratio (24), and the alteration of activation markers in specific populations of immune cells after their contact with the affected esophageal mucosa (26). What is more, the peripheral eosinophil count has been proposed as a possible predictor of PPI response (27), but none of the parameters described above is being used as biomarker for EoE diagnosis and improvement of therapy selection.…”
Section: Introductionmentioning
confidence: 99%
“…Also, single cell studies unraveled an enrichment in CD4 + T regulatory and Th 2 effector cells in the inflamed esophageal tissue (25). With the aim of exploring non-invasive biomarkers, the studies done in peripheral blood mononuclear cells (PBMCs) in active EoE patients demonstrated an increase in circulating CD4 + /CD8 + Tcell ratio (24), and the alteration of activation markers in specific populations of immune cells after their contact with the affected esophageal mucosa (26). What is more, the peripheral eosinophil count has been proposed as a possible predictor of PPI response (27), but none of the parameters described above is being used as biomarker for EoE diagnosis and improvement of therapy selection.…”
Section: Introductionmentioning
confidence: 99%